Assessing the impact of patient access to clinical notes on clinician EHR documentation. (13th July 2022) - Holmgren, A Jay; Apathy, Nate C
Abstract: Recent policy changes have required health care delivery organizations provide patients electronic access to their clinical notes free of charge. There is concern that this could have an unintended consequence of increased electronic health record (EHR) work as clinicians may feel the need to adapt their documentation practices in light of their notes being accessible to patients, potentially exacerbating EHR-induced clinician burnout. Using a national, longitudinal data set consisting of all ambulatory care physicians and advance practice providers using an Epic Systems EHR, we used an interrupted time-series analysis to evaluate the immediate impact of the policy change on clinician note length and time spent documenting in the EHR. We found no evidence of a change in note length or time spent writing notes following the implementation of the policy, suggesting patient access to clinical notes did not increase documentation workload for clinicians.